Investigating the Optimal Duration of the Sun Exposure for Adequate Cutaneous Synthesis of Vitamin D3 in Baghdad City: Depending on Fitzpatrick Skin Classification for Different Skin Types - Al-Timime, Noor S.; Al-Salihi, Ali M.; Hameed, Ahmed A. (Iraqi Journal of Science, 2024)
Vitamin D3 deficiency is regarded as a public health issue in Iraq, particularly during the winter. Sun exposure is the main source of vitamin D3, where the surface ultraviolet (UV) radiation plays an important role in human health. The amount of time that must be spent in the sun each day was determined for the amount of exposed skin, for all skin types, with and without sunscreen under clear sky conditions in the city of Baghdad (Long 44.375, Lat 33.375). UV index data was obtained by TEMIS satellite during the year 2021. From data analysis, we found that most days during the year were within the high level of ultraviolet radiation values ​​in the city of Baghdad, and most of them were during the summer, where the person needed less time of exposure to sunlight to obtain vitamin D3 in the case of exposing the face and hands or the whole body. As a result, it can be concluded that the amount of UV radiation is affected by several factors: depending on latitude, day of the year, time of day and the season, body area exposed to the radiation, and use of sun protection factor. These factors influence the time of sun exposure required to initiate cutaneous vitamin D3 synthesis.